Ecological disjunction across the sexes in an alloparasitoid: Host requirements, sex ratios and mate localization (Hymenoptera: Aphelinidae). Issue 3 (16th July 2019) - Abeeluck, Dav; Walter, Gimme H.
Abstract: The larval females of Coccophagus sp. nr gurneyi Compere are primary parasitoids of lantana mealybugs, whereas males develop hyperparasitically through other parasitoids (never their own females), so the species is alloparasitic. Males are seldom even reared from lantana mealybugs (<0.3%, n = 4, 212), and have not yet been reared from any other host. Adults were sampled in the field to establish that this species is sexual (by assessing female spermathecal content), and to quantify relative abundance of the sexes around host infestations. Adult males were scarce above hosts (3%, n = 314), but were attracted in relatively high numbers to caged virgin females within those infestations. Caged females outside infestations did not attract males, suggesting that mate attraction requires environmental signals other than those from females. Most females collected in the field above host infestations had sperm in their spermathecal capsules. They presumably had mated with males that developed elsewhere (so mate localization might involve searching across substantial distances). Virgin females were present only early in the day and evidently mate soon after eclosion. Evidence of sperm depletion in mated females was not found. The spatial scale of male and female movements needs to be quantified, but the ongoing movement of individuals (as a consequence of their sex‐related host relationships) seems to be a regular aspect of their ecology. The spatial and temporal dynamics across the sexes illustrates that their abilities to localize one another for mating leaves the sexes free to diverge ecologically, and their sex ratios to vary. Abstract : The ecology of males of the aphelinid wasp Coccophagus sp. nr gurneyi is fundamentally different from that of their conspecific females, as they develop in different types of hosts. The females emerge in areas that are spatially separate from the males. Their activity patterns indicate how they locate one another for mating and this has implications for interpreting their sex ratios and the background to the sexes diverging in their host relationships.